KONSEP AKAL (SUATU ANALISIS TERHADAP PEMIKIRAN Al-FARABI DAN IBNU SINA) - Juwaini Juwaini; Nik Yusri bin Musa (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2010)
The intellect capacity of human’s being is one of the common theme discussed in classical Islamic scholarly discourses, the philosophers also have been involved in the discussion. Variousverses in the Qur'an mentioned that every Muslim ought to maximize the use of their intellect. However, many genius people are still reluctant to use their intellect because of worried of getting going over the boundaries that allowed by religious teaching. But many people are so confident with their ability to include their rational reason as the measurement the truth. TheQur'an really appreciates the human’s intellect, therefore the Book Syar'i (Law of God) is only addressed to the people with their intellect capacity. Beside, many verses of the Koran and hadiths have encouraged people to use their intellects and showed the position of reason in Islamic law.